Prevalence And Antibiogram Of Bacterial Pathogens Isolated From Canine Pyoderma - Senapati, S.K.; Patra, R.C.; Panda , H.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
In the present study bacteriological examination was carried out on 85 superficial skin swab collected from different breeds of dogs suffering from superficial to deep pyoderma . Eight different species of bacteria were isolated from the 85 infected skin swabs. Mixed infection ofGram +ve and Gram –ve organisms were detected .Staphylococosaureus (85.8%) and Enterobacteraerogene (38.8%) were the predominant Gram +ve and Gram –ve bacteria isolated in the culture . On invitroantibiogram study, Ceftriaxone tazobactum, Amoxicillin-Clavulinic acid, Chloramphenicol, Levofloxacin, Framycetin and Mupirocin were found to be most sensitive with 100% efficacy against both Gram +ve and Gram –ve organism.